Handbook of health economics - Arrow, Kenneth J (Ed.); Intriligator, Michael D (Ed.) (Amsterdam Elsevier, 2000)
The handbook of health economics is in two volumes.The firstvol.A contents are-Overviews and paradigms,demand and reimbursements for medical services and insurance markets and the vol.B contents are-specfic population,the medical care market,law and regul
Keywords: MEDICAL ECONOMICS-HANDBOOKS, MANUALS, ETC